Effect of quantity and quality of pre-exercise carbohydrate meals on central fatigue - Khong, T. K.; Selvanayagam, V. S.; Hamzah, S. H.; Yusof, A. (Journal of Applied Physiology, 2018)
Both the quantity and quality of pre-exercise carbohydrate (CHO) meals have been shown to improve endurance performance. However, their role in attenuating central fatigue (CF) is inconclusive. The use of neurophysiological techniques, such as voluntary activation (VA) and the central activation ratio (CAR), alongside maximum voluntary contraction (MVC) and sustained MVC (sMVC) can provide information on CF. Hence, the objective of this study was to investigate the effects of isocaloric pre-exercise meals: 1) a high versus low quantity of CHO and 2) a high quantity of CHO with a high versus low glycemic index (GI) on MVC, VA, and CAR following a 90-min run. The high and low quantity of CHO was 1.5 and 0.8 g/kg body wt, respectively, and high and low GI was ~75 and ~40, respectively. Blood insulin, serotonin, tryptophan, and gaseous exchange were also measured. High CHO preserved sMVC, VA, CAR, and serotonin postrunning with greater CHO oxidation and insulin response, whereas in low CHO, greater reductions in sMVC, VA, and CAR were accompanied by higher serotonin and fat oxidation with lower insulin response. These observations indicate central involvements. Meanwhile, high GI CHO better preserved force (sMVC), CAR, and tryptophan with greater CHO oxidation and insulin response compared with low GI. The findings of this study suggest that pre-exercise meals with varying quantity and quality of CHO can have an effect on CF, where greater CHO oxidation and insulin response found in both high CHO and high GI lead to attenuation of CF. NEW & NOTEWORTHY This paper examined the effects of carbohydrate interventions (high and low: quantity and quality wise) on central activity during prolonged exercise using mainly neurophysiological techniques along with gaseous exchange and blood insulin, serotonin, and tryptophan data.